(untitled) - Dijk, Hanneke van; Shoeijer, Wim; Kurpershoek, Mineke; Otter, George M. (REBO Publishers, 2001)
In A to Z order, this encyclopedia describes bulbous and tuberous plants.
Includes index.
9-12
Keywords: Encyclopedias; Plants; Encyclopedias; Bulbs